A Comparative Study of Individual Freedom and Government Power in the Political Thought of Ayatollah Naeini and Sheikh Fazlullah Nouri - Valliolah Esfandiar; Garineh Keshishyan Siraki; Abdolrahman Hassanifar; Mohammadsalar Kasraei (پژوهش‌های تاریخی ایران و اسلام, 2020)
The individual freedom and government power have been among the concepts and issues discussed between the various political and religious currents during the constitutional period. Against the constitutional movement, one of the basic principles of which is the individual freedom and government power. Sheikh Fazlullah Nouri and Mirza Naeini, as representatives of the two important currents of thought, confronted each other and offered different views. It seems that most of the differences go back to the political foundations and ideas of individuals, but in fact, the differences between the scholars of the constitutional era are mainly in the analysis of political currents, comments on individuals and parties, motives. There were such cases, and it was natural that there would be disagreement in discussing such matters and commenting on these cases. In a comparative study using this method of comparative research, this article discusses the ideas and positions of the legitimate constitutional current and its main leader, Sheikh Fazlullah Nouri, against the constitutionalist scholars and its main leader, Allameh Naeini.